Reduction in initiations of HIV treatment in South Africa during the COVID pandemic - Mariet Benade; Lawrence Long; Sydney Rosen; Gesine Meyer-Rath; Jeanne-Marie Tucker; Jacqui Miot (BMC, 2022)
Abstract Background In response to the global pandemic of COVID-19, countries around the world began imposing stay-at-home orders, restrictions on transport, and closures of businesses in early 2020. South Africa implemented a strict lockdown in March 2020 before its first COVID-19 wave started, gradually lifted restrictions between May and September 2020, and then re-imposed restrictions in December 2020 in response to its second wave. There is concern that COVID-19-related morbidity and mortality, fear of transmission, and government responses may have led to a reduction in antiretroviral treatment (ART) initiations for HIV-infected individuals in countries like South Africa. Methods We analyzed national, public sector, facility-level data from South Africa's District Health Information System (DHIS) from January 2019 to March 2021 to quantify changes in ART initiation rates stratified by province, setting, facility size and type and compared the timing of these changes to COVID-19 case numbers and government lockdown levels. We excluded facilities with missing data, mobile clinics, and correctional facilities. We estimated the total number of ART initiations per study month for each stratum and compared monthly totals, by year. Results At the 2471 facilities in the final data set (59% of all ART sites in the DHIS), 28% fewer initiations occurred in 2020 than in 2019. Numbers of ART initiations declined sharply in all provinces in April-June 2020, compared to the same months in 2019, and remained low for the rest of 2020, with some recovery between COVID-19 waves in October 2020 and possible improvement beginning in March 2021. Percentage reductions were largest in district hospitals, larger facilities, and urban areas. After the initial decline in April-June 2020, most provinces experienced a clear inverse relationship between COVID-19 cases and ART initiations but little relationship between ART initiations and lockdown level. Conclusions The COVID-19 pandemic and responses to it resulted in substantial declines in the number of HIV-infected individuals starting treatment in South Africa, with no recovery of numbers during 2020. These delays may lead to worse treatment outcomes for those with HIV and potentially higher HIV transmission. Exceptional effort will be needed to sustain gains in combatting HIV.